Evaluation of exterior sanitary garments for meat plant employees for control of microbial contamination - G.V. Hickey; J.M. Bieker; E.J. Harvey; L.J. Franken; James L. Marsden; Randall K. Phebus; Curtis L. Kastner (Kansas Agricultural Experiment Station Research Reports, 2005)
Disposable frocks, manufactured by Precise Systems, LLC, and made of an innovative clothing material formed by an inner layer of a spun-bond polypropylene material reinforced by an outer layer of polyethylene, were compared with the cotton/polyester materials used in frocks typically worn in food plants today. The growth and absorption of bacteria on these materials were compared as an indicator of the sanitary conditions of the disposable frocks. These materials were cut into 2 x 2- inch pieces and were inoculated with generic Escherichia coli, E. coli O157:H7, Listeria monocytogenes, and Salmonella spp. Samples were collected after allowing microorganisms to attach for 0, 1, 2, 4, 6 and 8 hours. In most instances, the cotton/polyester absorbed and maintained the initial inoculation rate over the sampling times. Polypropylene was somewhat absorbent, but contamination rates were slightly lower than on cotton/polyester. Polyethylene material was non-absorbent and performed the best, especially with Listeria monocytogenes. The data indicate that the non-absorbent property of polyethylene does not provide a reservoir for microorganisms, allows run-off, and therefore potentially reduces the opportunity for cross-contamination of food products.
Keywords: Cattlemen' s Day; 2005; Kansas Agricultural Experiment Station contribution; no. 05-144-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 943; Beef; Sanitary garments; Microbial contamination